2020
DOI: 10.3389/fmicb.2020.01219
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics Uncovers the Genetic Diversity and Characters of Veillonella atypica and Provides Insights Into Its Potential Applications

Abstract: Veillonella atypica is a bacterium that is present in the gut and the oral cavity of mammals and plays diverse roles in different niches. A recent study demonstrated that Veillonella is highly associated with marathon running and approved that V. atypica gavage improves treadmill run time in mice, revealing that V. atypica has a high biotechnological potential in improving athlete performance. However, a comprehensive analysis of the genetic diversity, function traits, and genome editing method of V. atypica r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…In general, ethnicity and lifestyle have no effect on DAR profiles. These results also suggested that the structure of the dominant species in the Chinese gut microbiome might be stable and not affected by ethnicities or lifestyles, possibly because these species (i.e., Eubacterium rectale , Faecalibacterium prausnitzii , and Veillonella atypical ) are related to important functions (i.e., metabolism) ( Sokol et al, 2008 ; Berni Canani et al, 2012 ; Han et al, 2020 ). Moreover, there were significant differences only at the species level and none at higher taxonomy levels.…”
Section: Conclusion and Discussionmentioning
confidence: 84%
“…In general, ethnicity and lifestyle have no effect on DAR profiles. These results also suggested that the structure of the dominant species in the Chinese gut microbiome might be stable and not affected by ethnicities or lifestyles, possibly because these species (i.e., Eubacterium rectale , Faecalibacterium prausnitzii , and Veillonella atypical ) are related to important functions (i.e., metabolism) ( Sokol et al, 2008 ; Berni Canani et al, 2012 ; Han et al, 2020 ). Moreover, there were significant differences only at the species level and none at higher taxonomy levels.…”
Section: Conclusion and Discussionmentioning
confidence: 84%
“…Prevotella melaninogenica is commonly cultured as the sole infectious agent in extraoral abscesses such as spondylitis, osteomyelitis, pyomyositis, peritoneal abscesses and vaginal mesh infections ( 33 ). Veillonella members are frequently associated with mixed infections and are recovered mixed with mouth and bowel flora ( 34 ). Consistent with this report, we found that Veillonellaceae and Veillonella were positively correlated with serum ALP and GGT, adding to evidence of harmful effects of these bacteria on PBC.…”
Section: Discussionmentioning
confidence: 99%
“…Veillonella are anaerobic, gram negative cocci commonly found in the oral cavity, gut and vaginal tract that play diverse roles in different niches 42 . The pathogenic role of Veillonella is uncertain and they are currently considered to be of low virulence 43,44 . While Veillonella species have been associated with more diverse microbial communities, including the formation of biofilms leading to dental plaques in the oral cavity and serious infections such as endocarditis 45 , they have also been found to be more abundant in HPV negative women compared to HPV positive women 13,46 , as well as in the oral microbiota of HPV negative infants compared to the oral microbiota of HPV positive infants 46 .…”
Section: Discussionmentioning
confidence: 99%